The Principle of Utilization of Rahn in Non-Cash Transaction of Gold at Islamic Banks - Ali, Moh.; Rahma, Siska Hidayatur (Lentera Hukum, 2019)
Non-cash transaction of gold is one type of service by Islamic banks. Non-cash transactions of gold using the contract as a binder between Islamic banks and customers. The contract consists of a murabahah and rahn contract; this contract is contained in a Proof of Ownership of Gold (SBKE). In the rahn contract, there is a stipulation that gold, which is the object of cash, is used as collateral for Islamic banks. This study aims to analyze the validity and suitability of the rahn contract and future conceptions of noncash transactions of gold trading using the principle of benefit. The results showed that the rahn contract on the non-cash transaction of gold cash did not meet the validity of the contract contained in Article 21 KHES (Compilation of Sharia Economic Law) because there were provisions that contradicted Article 18 paragraph (1) item h of Law Number 8 of 1998 about Consumer Protection. Rahn in the non-cash transaction of gold is generally the same as the pawn only in the non-cash transaction of gold; there is an initial transaction in the form of murabahah. The next conception regarding the sale and purchase of gold in cash is a guarantee used no longer in the form of gold, but in the form of proof of ownership of gold or gold certificate, this is based on the MUI DSN fatwa Number 68 / DSN-MUI / III / 2008 concerning (rahn) Tasjily. Keywords: Non-cash Transaction of Gold, Rahn Contract, Principle of Utility